Garnet Geochemistry of Pertek Skarns (Tunceli, Turkey) and U-Pb Age Findings - Kilic, Ayse Didem; Konakci, Nevin; Sasmaz, Ahmet (Mdpi, 2024)
The Fe skarn and vein-type Cu mineralization types are common in the Eastern Taurus Mountains. This study aims to determine the U-Pb geochronology of garnets of varying sizes within the skarn zone developed at the quartz diorite-marble contact zone in Ayazp & imath;nar, Pertek District, Tunceli Province, Turkey. Additionally, this study aims to determine the age of the skarnization and the types of inclusion minerals in the garnets. Faulting and magma emplacement along the thrust plane caused mineralization in the Eastern Taurus Mountains, especially at the marble and quartz diorite contact zone between the cities of Elaz & imath;& gbreve; and Tunceli. The greenish garnets found in the Ayazp & imath;nar deposit are characteristic of distal skarns, while red or brown Pertek garnets are observed in the proximal skarns. The garnets typically feature a core-rim texture. The cores of the garnet crystals are large, reddish in color, and have a high REE (Ce, Pr) content. Moreover, the cores have higher Fe and lower Al ratios, alongside higher La, Ce, and Pr contents, than the rims. We propose that the compositional differences between the rims and the cores reflect the transition from oxidized REE- and Fe3+-rich liquids to liquids with lower REE and Fe3+ contents, producing the differences in the garnet colors. Green garnets show lower REE contents than brown garnets with Fe-rich cores. The skarn under study includes the following successively formed zones: diorite -> epidote skarn -> garnet-magnetite -> pyrite-garnet-magnetite -> calcite carbonate. Diopside, magnetite, and hematite, including small grains, are surrounded or enveloped by garnets. The U-Pb age of the mineralization is 74.1 +/- 5 Ma, indicating that the mineralization occurred concurrently with the intrusion settlement.
Keywords: garnet; U-Pb geochronology; skarn; ore-forming fluid; REE